Genetic and Physiological Characterisation of Oenococcus oeni Strains to Perform Malolactic Fermentation in Wines - Renouf, V.; Favier, M. (South African Journal of Enology and Viticulture, 2016)
Malolactic fermentation (MLF) is a process that is increasingly conducted by Oenococcus oeni industrial strains. Recently, studies of the diversity of O. oeni strains have developed some potential genetic tools to characterise the abilities of the strains. During this work, a mutation on a partial sequence of the rpoB gene and the presence of some genes previously established to be present in the most performing strains were tested on some strains that are already marketed and some potential new strains. These tests were compared with a physiological test never previously taken into account: the tolerance to octanoic and decanoic acid, important inhibitory compounds in wines. Our objectives were to compare the relevance of the genetic tests currently available, that of resistance to medium chain fatty acids and the results of winemaking. Ultimately, it is clear that, as far as current knowledge is concerned, genetic tests are not yet sufficient to completely characterise the strain potential, and physiological tests therefore are always needed. The resistance to medium chain fatty acids is an interesting point to be considered to explain the difficulty that some strains have to resist inoculation in wine. But other criteria should also be characterised better, such as the duration of the latent phase between inoculation and the beginning of MLF, and the rate of degradation of malic acid by the different strains.